Optimalization Business Management for Catfish Farmers Community in Polowidi Village - Anindya, Khoirina Noor; Tatik, Tatik (PT FORMOSA CENDEKIA GLOBAL, 2023)
The catfish farmers community in Polowidi village, Sleman regency, Daerah Istimewa Yogyakarta (DIY) is a community of farmers who develop land around their houses which can be used as medium to breed catfish, but the lack of business management especially in developing pond, marketing, and capital access become the problems in this activity. This community service aims are giving knowledge and upgrading ability of catfish farmers to improve the business management by implementing 4 programs. The first is development of pond by using tarpaulins. The second is training of social media marketing and capital access. The third is mentoring the business activity. The fourth is following up program to improve the catfish farmers ability in the future.